Therapeutic and diagnostic potential of extracellular vesicles in amyotrophic lateral sclerosis - Taylor J. Ellison; Steven L. Stice; Yao Yao (Extracellular Vesicle)
As a late-onset and fatal neurodegenerative disease that affects upper and lower motor neurons, amyotrophic lateral sclerosis (ALS) is a difficult disease to diagnose and treat, needing further research on mechanisms of pathogenesis. In addition due to difficulties in delivering therapeutics past the blood brain barrier (BBB) to target disease-relevant cells in the central nervous system (CNS), diseases like ALS are particularly difficult to manage. However, recent advances in nanomedicine have provided new opportunities. Extracellular vesicles (EVs) are small, spherical, nanosized particles that have shown various applicable properties in the treatment and diagnosis of ALS through inherent characteristics and drug delivery capabilities. Extracellular vesicles with unique cargos determined by cells of origin possess neural protecting qualities and can cross the BBB and deliver endogenous and/or engineered cargo to specific neural cell targets. In this review, we discuss the potential use of EVs as therapeutics, drug delivery systems, and biomarkers for ALS.